In vivo tibia lead measurements as an index of cumulative exposure in occupationally exposed subjects. Issue 3 (March 1988) - Somervaille, L J; Chettle, D R; Scott, M C; Tennant, D R; McKiernan, M J; Skilbeck, A; Trethowan, W N
Abstract : In vivo tibia lead measurements of 20 non-occupationally exposed and 190 occupationally exposed people drawn from three factories were made using a non-invasive x ray fluorescence technique in which characteristic x rays from lead are excited by gamma rays from a cadmium-109 source. The maximum skin dose to a small region of the shin was 0.45 mSv. The relation between tibia lead and blood lead was weak in workers from one factory (r = 0.11, p greater than 0.6) and among the non-occupationally exposed subjects (r = 0.07, p greater than 0.7); however, a stronger relation was observed in the other two factories (r = 0.45, p less than 0.0001 and r = 0.53, p less than 0.0001). Correlation coefficients between tibia lead and duration of employment were consistently higher at all three factories respectively (r = 0.86, p less than 0.0001; r = 0.61, p less than 0.0001; r = 0.80, p less than 0.0001). A strong relation was observed between tibia lead and a simple, time integrated, blood lead index among workers from the two factories from which blood lead histories were available. The regression equation from two groups of workers (n = 88, 79) did not significantly differ despite different exposure conditions. The correlation coefficient for the combined data set (n = 167) was 0.84 (p less than 0.0001). This shows clearly that tibia lead, measured in vivo by x-ray fluorescence, provides a good indicator of long term exposure to lead as assessed by a cumulative blood lead index.